Pengaruh Bauran Pemasaran Terhadap Keputusan Pembelian Sepeda Motor Honda Beat Pada PT Daya Anugrah Mandiri - Anugrah Ilahi, Andi Alfianto; Arfah, Aryati; Arif, Muhammad (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2023)
The purpose of this study was to find out how much influence Product, Price, Promotion and Place had on the Purchase Decision of a Honda Beat motorcycle using the SPSS 20 analysis method. The results showed that: 1. Product (X1) did not affect the purchase decision variable (Y) because tcount1.618≤ttable (2.085) and a significant probability of (0.003)≤ α (0.05). 2. Price (X2) does not affect the purchase decision variable (Y) because tcount 0.865 ≤ t table (2.085) and a significant probability of (0.005) ≤ α (0.05). 3. Promotion (X3) has a positive and significant effect on decisions purchase (Y) because tcount5.006≥ttable (2.085) and a significant probability of (0.000)≤ α (0.05). 4.Place (X4) has a positive and significant effect on purchasing decisions (Y) because tcount2.673≥ttable (2.085) and a significant probability of (0.001)≤ α (0.05).5. Product (X1) Price (X2) Promotion (X3) and Place (X4) have a positive (22.845) and significant (0.000 ≤ 0.05) effect on the Purchase Decision variable (Y) at PT. Daya Anugrah Mandiri Parepare Branch.